Legislative reflection on critical information infrastructure protection in China - UANGDao-li HUANG; Ting FANG (网络与信息安全学报)
The necessity of critical information infrastructure protection legislation is particularly prominent. Current legislations and practice show that critical information infrastructure protection is lack of a strong regulation at the national level, national and industry department lack of knowledge and ability to protect critical information infrastructure and their responsibilities are unclear with no effective coordination mechanisms, financial, technical and personnel support capabilities are also weak. To speed up the formulation and promulgation of critical information infrastructure protection legislation, the organization system and its working mechanism of critical information infrastructure protection should be clearly defined, and early warning and monitoring mechanism, emergency response and recovery mechanisms, security supervision system, accountability system and basic safeguard system should be built.